Biological mass spectrometry - Burlingame, A. L. (Methods in enzymology, 2005)
This volume describes and integrates the techniques and fundamentals of more than a decade of revolutionary advances in both chromatographic and mass spectrometric technologies that have enabled the direct investigation of biomacromolecules per se and have provided the analytical power base to usher in the new fields of proteomics and systems biology. It also covers new biophysical applications such as H/D exchange for study of conformations, protein-protein and protein-metal and ligand interactions. Finally it describes atto-to-zepto-mole quantitation of 14C and 3H by accelerator mass spectrometry. *Part 1 of 2 volumes about Mass Spectrometry *Authoritative and comprehensive treatment of protein mass spectrometry in human cell biology *Presents fundamentals, techniques, instrumentation and bioinformatics *Provides an overview of proteomics, protein-protein and protein-ligand binding, and biophysical studies.